MEDICATION ADHERENCE IN ELDERLY PATIENTS WITH HYPERTENSION - Athiyah, Umi; Subarniati, Rika; Yuda, Ana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: This study aimed to identify the relationship between knowledge and beliefs about drugs with adherence of drug use based on the health belief model (HBM) theory. Methods: Respondents were elderly hypertensive patients who received their medicine by prescription in one pharmacy in Surabaya. Knowledge and belief variables were measured by a validated questionnaire, while medication adherence was measured by pill count. Results: There were 57 respondents aged 60-88 years, 54.4% of which are female. A total of 57.9% of respondents used at least two kinds of anti-hypertension drugs and 54.4% had health problems other than hypertension. The results of Pearson analysis show that respondents’ knowledge about the drug had a significant relationship with perceived threat, perceived benefit (p=0.043), and perceived self-efficacy (p=0.015), but no significant relationship with adherence, while the result of Spearman analysis shows that only perceived barrier had a significant relationship to adherence (p=0.029). Conclusion: To conclude, efforts to improve adherence was to lower perceived barrier which was primarily associated with decreased physical ability and concerns about the dangers of long-term drug use.